2016
DOI: 10.3892/mco.2016.994
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3 expression in epithelial ovarian cancer exerts a minor effect on clinicopathological parameters

Abstract: Abstract. The role of trefoil factor 3 (intestinal) (TFF3) has been analyzed in numerous cancers, such as breast and gastrointestinal cancer, and has been associated with poor prognosis. However, the role of TFF3 in ovarian cancers is not clear. Expression analysis of TFF3 in 91 ovarian cancer patients was performed by immunohistochemistry of primary paraffin-embedded tumor samples. The results were scored according to staining intensity and percentage of positive tumor cells resulting in an immune-reactive sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Furthermore, we examined whether variation in the expression of certain genes contributed more to this latent variable than others. Using a gene set enrichment analysis (GSEA), we found an enrichment of genes with substantial contribution to this factor involved in estrogen response , including AGR2 and TFF3 (Figure 5b) (Salmans et al, 2013; Hoellen et al, 2016). These results suggest that there are substantial shared signals between the two data modalities, echoing prior work (Gundersen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we examined whether variation in the expression of certain genes contributed more to this latent variable than others. Using a gene set enrichment analysis (GSEA), we found an enrichment of genes with substantial contribution to this factor involved in estrogen response , including AGR2 and TFF3 (Figure 5b) (Salmans et al, 2013; Hoellen et al, 2016). These results suggest that there are substantial shared signals between the two data modalities, echoing prior work (Gundersen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression levels of TFF1 and TFF3 have been shown to correlate with changes in Ca125 (progression) and endocrine therapy response rates in ovarian cancer (56). Moreover, TMAbased studies demonstrated a correlation between elevated TFF3 expression, better prognosis, and lower recurrence rates in OC, but these studies were not stratified by histotype (54,57). In a study by Kalloger et al on OC histotyping, the TFF3 gene was used to separate different epithelial ovarian cancer subtypes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of elevated TFF1 protein levels in diverse cancers such as pancreatic, colonic, and ovarian tumor tissues indicate a universal function in tumor progression via stimulation of cell migration, survival, invasiveness, and distant spread ( 36 , 37 ). The TFF3 gene has been shown to be an estrogen-regulated oncogene with prognostic value in estrogen-positive breast cancer and important contributor to gastric cancer progression ( 54 ). In addition, high TFF3 levels are associated with poor survival, recurrence and distant metastasis in colorectal cancer ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a higher TFF3 expression was found in BOT mucinous histology and BOT with mixed histology, suggesting a potential function of the protein in these histological subtypes [37]. Expression analysis of TFF3 was performed in a cohort of 91 OC patients by Hoellen et al No significant difference in TFF3 expression was found based on age, FIGO stage or residual tumor; meanwhile, a significant correlation of TFF3 expression and grade was detected [48]. However, since few studies have been carried out on TFF3 expression and its role in EC and OC and, mostly, few studies have considered its prognostic value, TFF3 expression deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of analyzing the expression of Romo1 in EC and OC comes from the evidence of its role in the process of invasion and also the progression of cancer cells [35,48]. It is involved in normal cellular processes, such as cell proliferation, senescence, and death.…”
Section: Discussionmentioning
confidence: 99%